Kontribusi Nilai-Nilai Falsafah Dan Budaya Hidup Bangsa Jepang Bagi Kemajuan Pendidikan Jepang Pasca Perang Dunia II - Etmi Hardi; Azwar Ananda; Nurhizrah Gistituati; Rusdinal Rusdinal (UIN Fatmawati Sukarno Bengkulu, 2023)
Japan that was devastated in World War II, in a relatively short time was able to rebuild itself, becoming one of the new powers in the world, in the fields of science, technology and economy. Those all were achieved through their superior and quality education system, so that Japan became one of the countries with the best education system in the world. This article was written to explore the philosophical and cultural values of the Japanese nation that have an impact on the progress of education in the country. The method used was qualitative research based on library research (literature study). The data sources in this research came from various literatures in the form of books, articles (print and online) related to the research theme, as well as document materials in the form of policies issued by the Japanese Embassy. The research findings found that the rapid development of Japanese education could not be separated from the philosophical values of the Japanese nation which originated from Confucianism teaching. In addition, the Japanese culture of Ganbatte Kudasai as the embodiment of the Bushido philosophy also encouraged the development of Japanese education.